A gift, a bond, a prize that binds : examining scholarship awards in the era of ‘Ethical internationalisation’ - Saling, Kieve Stone ; 0000-0003-1238-9589 (Studies in Higher Education, 2024)
The paper examines preconceptions and assumptions behind common understandings of ‘scholarship awards’ in international higher education research, and analyses how these influence the production of knowledge on scholarship programs and their effects. The paper aims to make a major theoretical contribution by proposing an alternative approach to studying these programs. First, drawing on a comprehensive review of the scholarships literature, the paper posits that prevalent theoretical approaches–often drawn from the logic of the scholarship programs themselves–limit our view of what scholarship programs do and can do. Such research constrains understandings of program design and its effects on and implications for sponsored students. Examples of underexplored ethical aspects of sponsorship arrangements are highlighted through examples and vignettes. Then, turning to contemporary discussions related to ethical internationalisation and student mobility, the paper asks which theoretical approaches could aid a focus upon and analysis of these programs in relation to ethics-related themes. Conventions theory (and specifically the orders of worth approach) is proposed as a useful theoretical lens. The paper then synthesises a novel framework using this approach to examine explicit and implicit aspects of sponsorship arrangements, explaining its suitability and potential to produce deeper insights into and more nuanced understanding of the consequences of modern scholarship program design for actors involved in sponsored international student mobility. In conclusion, the promise and significance of this framework utilizing the orders of worth approach for studying questions related to valuation processes and ethical internationalisation is recapitulated and future research is discussed.
Publisher Copyright: © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: ethical internationalisation; international student mobility; orders of worth; Scholarships; sponsored students